Periodic Solutions Generated by Impulses for State-Dependent Impulsive Differential Equation - Qizhen Xiao; Binxiang Dai (Discrete Dynamics in Nature and Society)
We study the existence of periodic solutions for a class of state-dependent impulsive differential systems via geometrical analysis methods. Our results show that these periodic solutions are generated by impulses. Moreover, numerical simulations are used to examine the existence of the periodic solutions.